2017
DOI: 10.1590/2177-6709.22.5.056-066.oar
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the cranial base flexion on Class I, II and III malocclusions: a systematic review

Abstract: Objective: The aim of this study was to perform a systematic review on the morphological characteristics of the skull base (flexion, anterior length and posterior length) and the concomitant development of malocclusions, by comparing differences in dimorphism, ethnicity and age. Methods: The articles were selected by means of electronic search on BBO, MEDLINE and LILACS databases from 1966 to 2016. A qualitative evaluation of the methodologies used on the articles was also performed. Results: Although the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
2
19
0
3
Order By: Relevance
“…In addition, according to Bjork, the cranial base angle is 130.8° ± 4.2° at age 12 and 131.6° ± 4.5° at age 20 years, showing an insignificant change from the former age to the latter 34 . Almeida et al, in their systematic review showed that SNBa remains constant from 5 to 15 years of age 35 . Alió et al observed that in both individuals with DS and the general population it does not vary between the ages of 8-18 years 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to Bjork, the cranial base angle is 130.8° ± 4.2° at age 12 and 131.6° ± 4.5° at age 20 years, showing an insignificant change from the former age to the latter 34 . Almeida et al, in their systematic review showed that SNBa remains constant from 5 to 15 years of age 35 . Alió et al observed that in both individuals with DS and the general population it does not vary between the ages of 8-18 years 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Malocclusions with skeletal discrepancies in the craniofacial region to the cranial base as well as to each other. [5][6][7] Cranial base also plays a major role in defining various skeletal malocclusions. 8 According to Moss 9 cranial base angle in subjects of class III malocclusion is smaller and other studies…”
Section: Introductionmentioning
confidence: 99%
“…The maxillary length (A-Co) as well showed signifi cant difference between the three groups (P=0.030) with a higher [13,17].…”
Section: Maxillary and Mandibular Skeletal Parametersmentioning
confidence: 97%